A Z‐Scheme Strategy that Utilizes ZnIn2S4 and Hierarchical VS2 Microflowers with Improved Charge‐Carrier Dynamics for Superior Photoelectrochemical Water Oxidation. Issue 24 (9th July 2019) - Gogoi, Gaurangi; Moi, Ching Thian; Patra, Anindya Sundar; Gogoi, Devipriya; Rao, Peela Nageswara; Qureshi, Mohammad
Abstract: One of the major limiting factors for efficient photoelectrochemical water oxidation is the fast recombination kinetics of photogenerated charge carriers. Herein, we propose a model system that utilizes ZnIn2 S4 and hierarchical VS2 microflowers for efficient charge separation through a Z‐scheme pathway, without the need for an electron mediator. An impressive 18‐fold increase in photocurrent was observed for ZnIn2 S4 –VS2 compared to ZnIn2 S4 alone. The charge‐transfer dynamics in the composite were found to follow a Z‐scheme pathway, which resulted in decreased charge recombination and greater accumulation of the surface charge. Furthermore, slow kinetics of the surface reaction in the ZnIn2 S4 –VS2 composite correlated to an increased surface‐charge capacitance. This feature of the composite material facilitated partial storage of the photogenerated charge carriers (e − /h + ) under illumination and dark‐current conditions, thus storing and utilizing solar energy more efficiently. Abstract : You don't bring me microflowers : An extraordinary increase in photocurrent density (ca. 18 fold) was observed for the noble‐metal‐free, direct Z‐scheme composite material ZnIn2 S4 –VS2 . TCO=transparent conducting oxide, PEC=photoelectrochemical process.